Penerapan Restorative Justice Terhadap Pencurian Buah Kelapa Sawit Oleh Anak Di Bawah Umur (Studi Kasus Di PTPN IV Unit Air Batu) - Agung Nusa Pratidina; Marsella Marsella; Wessy Trisna (Universitas Medan Area, 2020)
Theft is one type of crime that often occurs wherever and whenever. Theft carried out by minors is not new, remembering that the age is still underage, Restorative justice is highly recommended to be applied in the settlement of the theft case. The research method used in this study is juridical empirical and the nature of the study using descriptive analytical research. Settlement of problems with the Implementation of the Restorative Justice Principle will make children aware of the wrong doing of children. Opening opportunities for dialogue between the perpetrators and their victims, a family-friendly approach like this is likely to be successful than sending children to justice, because processing children to justice will not guarantee the children's rights, it can even make children worse. The transfer of formal legal processes to non-formal settlement can be used as a reference for judges to settle children's cases, because it can provide maximum protection for the child's future. The form of settlement is first secured to the office of PTPN IV Air Batu, then with all the existing processes the child makes an agreement to the PTPN IV so as not to commit crimes again and create a deterrent effect for him.